KNOWLEDGE IS A KEY FACTOR IN A HEALTHY LIFE (Web of Teachers: Inderscience Research, 2024)
A well-educated person faithfully serves the rest of his life. Intelligent people do not have difficulty in life, and even in their hard-to-reach parts, they can rely on intelligence and choose the right path. Therefore, the most valuable thing in this bright world is intelligence, understanding, and discernment. The wise men did not say that if they wanted the wisdom of the world, you would find it in knowledge and know it well. The well-being of the family also depends on his knowledge.